(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2018)
We report a case of typhoid ulcer with severe life-threatening bleeding and discuss the management of this extremely uncommon entity. As a complication of typhoid fever, an eleven year old boy from Dhaka, Bangladesh developed massive fresh bleeding per rectum. Although there is no practical way of predicting the occurrence of such rare complications, we emphasize in this case report the wide array of pathologies that can result from typhoid fever. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (1): 38-40